Disclosure of Corporate Social Responsibility on Firm Value Trough Financial Performance - Akal, Andi Tenri Uleng; Gaffar, Samsu; R, Masmarulan; Basir, Muhammad; Mashuddin, Nurwahidah (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze corporate social responsibility disclosure to companies with financial performance as an intervening variable. This research is a quantitative research type. We conducted this study on the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange involving 13 companies. The type of data is secondary in the company's annual financial report. For data analysis using descriptive statistical techniques, classical assumption test, and multiple linear regression. The results of this study indicate that CSR disclosure has a negative and insignificant effect on firm value. At the same time, CSR disclosure negatively and significantly impacts financial performance. Based on the path analysis method, corporate social responsibility disclosure cannot affect company value and financial performance. We suggest that companies consistently implement CSR even though it does not affect company value because companies still have to manage the impacts that arise.